Corporate Governance : The Foundation for Corporate Citizenship and Sustainable Businesses - International Finance Corporation; UN Global Compact (Washington, DC, 2017)
Corporate citizenship - a commitment to ethical behavior in business strategy, operations, and culture - has been on the periphery of corporate governance and board leadership, linked mainly to corporate reputation. However, in today’s globalized and interconnected world, investors, creditors, and other stakeholders have come to recognize that environmental, social, and governance responsibilities of a company are integral to its performance and long-term sustainability. Today, these concerns help determine profits. For companies to operate successfully and sustain growth, boards must incorporate these new dimensions into their core decision making processes. The global financial crisis has heightened the need for corporate boards of directors to provide well-informed strategic direction and engaged oversight that stretches beyond short-term financial performance. A new vision of business is emerging - one where a set of core values, encompassing human rights, environmental protection, and anti-corruption measures, guide the board’s oversight, relationship with management, and accountability to shareowners. Good corporate governance is the glue that holds together responsible business practices, which ensures positive workplace management, marketplace responsibility, environmental stewardship, community engagement, and sustained financial performance. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.